2020
DOI: 10.3390/nano10030461
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis of Mn3O4 Nanowires and Application in the Treatment of Phenol at Room Temperature

Abstract: Nanosized Mn3O4 nanowires are prepared with KMnO4 and ethanol in mild conditions by facile hydrothermal method. Hydrothermal reaction temperature is optimized to get uniform nanowires. The prepared Mn3O4 nanowires exhibit high activity in the treatment of phenol at acid condition and room temperature. The 20 mg Mn3O4 nanowires can efficiently dispose of 50 mL phenol solution (0.2 g·L−1) at pH 2 and 25 °C. The nanowires before and after phenol treatment are characterized by scanning electron microscopy (SEM), X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…It was also observed that this structure was more distinct in catalyst prepared by pentane aided impregnation, as identified by the zoomed in area in Figure 2D2 . This fibril-like structure resembles the reported SEM images of manganese oxide (Mn 3 O 4 ) and mixed Fe-Mn oxide (FeMnO 3 ) crystallites [ 38 , 39 ] as well as carbon fibrils [ 40 ]. For identification of these structures, EDS analysis data along with SEM images were evaluated.…”
Section: Resultssupporting
confidence: 81%
“…It was also observed that this structure was more distinct in catalyst prepared by pentane aided impregnation, as identified by the zoomed in area in Figure 2D2 . This fibril-like structure resembles the reported SEM images of manganese oxide (Mn 3 O 4 ) and mixed Fe-Mn oxide (FeMnO 3 ) crystallites [ 38 , 39 ] as well as carbon fibrils [ 40 ]. For identification of these structures, EDS analysis data along with SEM images were evaluated.…”
Section: Resultssupporting
confidence: 81%
“…Mn 3 O 4 nanorods are promising heterogeneous Fenton-type catalysts, , but their catalytic performance are still restricted by the low H 2 O 2 utilization efficiency, which is associated with the extremely low lifetime of • OH in water and the mass-transfer limitation . Very recently, Zhang et al demonstrated that spatial confinement of Fenton chemistry at the nanoscale can significantly enhance the kinetics of radical-mediated oxidation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption is considered as the one of the best techniques in waste water treatment and gas separation due to the simplicity in set-up and cost efficiency [ 17 , 18 ]. Porous materials with high surface area and strong binding affinity are very promising candidates for sustainable and clean water supply in the future [ 19 , 20 ]. It has been demonstrated that the transition metals have obvious effect on the AlPO-5 zeolite adsorption capacity and the ZnAPO-5 showed higher adsorption capacity for all xylene isomers [ 21 ].…”
Section: Introductionmentioning
confidence: 99%